Are Mega-Farms the Future of Global Agriculture? Exploring the Farm Size-Productivity Relationship for Large Commercial Farms in Ukraine - Deininger, Klaus; Nizalov, Denys; Singh, Sudhir K. (World Bank, Washington, D.C., 2013)
With farms cultivating tens or hundreds of thousands of hectares, Ukraine is often used to demonstrate the existence of economies of scale in modern grain production. Panel data analysis for all the country's farms with more than 200 hectares in 2001-2011 suggests that higher yields and profits are due to unobserved factors at rayon (district) and farm level rather than economies of scale. Productivity growth was driven not by farm expansion but by exit of unproductive and entry of more efficient farms. Higher initial shares of area under farms with more than 3,000 or 5,000 hectares at the rayon level significantly reduce subsequent exit, suggesting that land concentration reduces productivity growth. The paper draws implications for global evolution of farm structures.